Small Footprint Mix-Column Serial for PHOTON and LED Lightweight Cryptography - Abbas Y.A.; Jidin R.; Jamil N.; Zraba M.R.; Al-Azawi S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Comparator circuits; Comparators (optical); Cryptography; Field programmable gate arrays (FPGA); Photons; Table lookup; Hardware implementations; Light-weight cryptography; Logical operations; Matrix manipulation; MAtrix multiplication; Mixcolumns; Polynomial multiplication; Small footprints; Light emitting diodes